The sustainable sites handbook : a complete guide to the principles, strategies, and practices for sustainable landscapes - Calkins, Meg, 1965- (Hoboken, N.J. : Wiley, 2012)
'This official reference guide to the Sustainable Sites Initiative Rating System contains information on principles, strategies, technologies, tools, and best practices for sustainable site design applicable to any type of designed landscape, with or without buildings, ranging from shopping malls, streetscapes, subdivisions, corporate and academic campuses, transportation corridors, parks and recreation areas, all the way to single family homes. Equally useful as a guide to achieving SSI credits, or as a guide to independent pursuit of sustainable sites, it offers in-depth coverage on important'green' topics'--
'This book will be the official reference guide to Sustainable Sites Initiative Rating System, the first national rating system for sustainable landscapes'--
Includes bibliographical references and index.
Keywords: Sustainable Sites Initiative; Landscape ecology -- Handbooks, manuals, etc; Sustainable development -- Evaluation -- Handbooks, manuals, etc; Environmental management -- Evaluation -- Handbooks, manuals, etc; ARCHITECTURE / Landscape